Neuropilin-2 and its ligand VEGF-C predict treatment response after transurethral resection and radiochemotherapy in bladder cancer patients - Keck, Bastian; Wach, S.; Taubert, Helge; Zeiler, S.; Ott, O. J.; Kunath, F.; Hartmann, Arndt; Bertz, Simone; Weiss, C.; Hoenscheid, P.; Schellenburg, S.; Roedel, C.; et al. (International Journal of Cancer, 2015)
The standard treatment for invasive bladder cancer is radical cystectomy. In selected patients, bladder-sparing therapy can be performed by transurethral resection (TURBT) and radio-chemotherapy (RCT) or radiotherapy (RT). Our published in vitro data suggest that the Neuropilin-2 (NRP2)/VEGF-C axis plays a role in therapy resistance. Therefore, we studied the prognostic impact of NRP2 and VEGF-C in 247 bladder cancer patients (cN0M0) treated with TURBT and RCT (n = 198) or RT (n = 49) and a follow-up time up to 15 years. A tissue microarray was analyzed by immunohistochemistry. NRP2 expression emerged as a prognostic factor in overall survival (OS; HR: 3.42; 95% CI: 1.48 - 7.86; p = 0.004) and was associated with a 3.85-fold increased risk of an early cancer specific death (95% CI: 0.91 - 16.24; p = 0.066) in multivariate analyses. Cancer specific survival (CSS) dropped from 166 months to 85 months when NRP2 was highly expressed (p = 0.037). Patients with high VEGF-C expression have a 2.29-fold increased risk of shorter CSS (95% CI: 1.03-5.35; p = 0.043) in univariate analysis. CSS dropped from 170 months to 88 months in the case of high VEGF-C expression (p = 0.041). Additionally, NRP2 and VEGF-C coexpression is a prognostic marker for OS in multivariate models (HR: 7.54; 95% CI: 1.57-36.23; p = 0.012). Stratification for muscle invasiveness (T1 vs. T2-T4) confirmed the prognostic role of NRP2 and NRP2/VEGF-C co-expression in patients with T2-T4 but also with high risk T1 disease. In conclusion, immunohistochemistry for NRP2 and VEGF-C has been determined to predict therapy outcome in bladder cancer patients prior to TURBT and RCT.
EVALuna2:6641